2015
DOI: 10.4103/1117-6806.162572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical parameters and challenges of managing cervicofacial necrotizing fasciitis in a Sub-Saharan tertiary hospital

Abstract: Introduction:Necrotizing fasciitis is a severe soft tissue infection. In our environment, patients presenting with this infection are usually financially incapacitated and, therefore, their management can be challenging. This paper aimed to document the pattern and challenges encountered in the management of cervicofacial necrotizing fasciitis (CNF) in the University College Hospital, Ibadan.Materials and Methods:Information such as biodata, site of infection, systemic conditions, widest span of defect, manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Most of the available literature on cervicofacial NF is largely based on western countries where delay in seeking medical care, lack of personnel, self-prescription and poor nutrition are not common problems. Except for a few [4, 17, 18], the existing literature consists almost entirely of individual case reports and several small case series, which do not adequately permit reporting of patterns of presentation and management.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the available literature on cervicofacial NF is largely based on western countries where delay in seeking medical care, lack of personnel, self-prescription and poor nutrition are not common problems. Except for a few [4, 17, 18], the existing literature consists almost entirely of individual case reports and several small case series, which do not adequately permit reporting of patterns of presentation and management.…”
Section: Introductionmentioning
confidence: 99%
“…11 The largest study from a single health center in Nigeria reported that there is a definite rise in prevalence of necrotizing fasciitis as they have seen a gradual increase to around 4 cases a year. 6 A systematic review conducted by Dhanasekana et al on necrotizing soft tissue infections from across the globe, found that the most common organisms involved are Staphylococcus aureus followed by Streptococcus pygenes and E. coli in North America, Asia, Middle East, and Africa. Interestingly, 16% of necrotizing soft tissue infections were accounted for by Methicillinresistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3] It mainly affects those of immunocompromised and low socioeconomical status. [2][3][4][5][6] According to the Joint United Nations Programme on HIV/AIDS (UNAIDS) it's estimated that 7 800 000 people in South Africa are living with Human Immunodeficiency Virus (HIV). 7 Due to the high prevalence of HIV in this population, knowledge and swift intervention of this condition is of importance .…”
Section: Introductionmentioning
confidence: 99%
“…7 Reported predisposing factors for CNF include immunosuppression, diabetes mellitus, chronic illnesses, malnutrition, advanced age, renal insufficiency, malignancies, burns, arteriosclerosis, anaemia, smoking, alcoholism, obesity, hypothyroidism and drug use. 21 NF typically involves poly-microbial infections, with haemolytic Streptococcus A and Staphylococcus spp. being the most commonly isolated pathogens, alongside facultative aerobic and anaerobic bacteria.…”
Section: Introductionmentioning
confidence: 99%